2015
DOI: 10.1021/acs.biomac.5b01434
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembly of Supported Lipid Bilayer Poly-l-Lysine Multilayers

Abstract: Multilayer lipid membranes perform many important functions in biology, such as electrical isolation (myelination of axons), increased surface area for biocatalytic purposes (thylakoid grana and mitochondrial cristae), and sequential processing (golgi cisternae). Here we develop a simple layer-by-layer methodology to form lipid multilayers via vesicle rupture onto existing supported lipid bilayers (SLBs) using poly l-lysine (PLL) as an electrostatic polymer linker. The assembly process was monitored at the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Figure A shows a series of cyclic voltammograms (CVs) of the SAM only, a 1:1 (w/w) POPC/POPG base membrane containing 1.5% (w/w) MQ7 and then each response after four cycles of incubation with PLL followed by 3:1 POPC/POPG 1.5% (w/w) MQ7 vesicles. These lipid compositions were chosen since we have previously shown that this protocol creates additional membranes with each PLL/vesicle incubation cycle on mica, glass, and SiO 2 . The CV of the first bilayer shows the MQ7 reduction (≈−0.45 V vs standard hydrogen electrode, SHE) followed by oxidation (≈0.1 V vs SHE) peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure A shows a series of cyclic voltammograms (CVs) of the SAM only, a 1:1 (w/w) POPC/POPG base membrane containing 1.5% (w/w) MQ7 and then each response after four cycles of incubation with PLL followed by 3:1 POPC/POPG 1.5% (w/w) MQ7 vesicles. These lipid compositions were chosen since we have previously shown that this protocol creates additional membranes with each PLL/vesicle incubation cycle on mica, glass, and SiO 2 . The CV of the first bilayer shows the MQ7 reduction (≈−0.45 V vs standard hydrogen electrode, SHE) followed by oxidation (≈0.1 V vs SHE) peaks.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported on a simple layer‐by‐layer (LBL) methodology to form lipid multilayers via vesicle rupture onto existing SLBs using poly‐ l ‐lysine (PLL) as an electrostatic polymer “glue.” Not only does this technique allow incorporation of membrane proteins, but it can also create membrane stacks with different membrane proteins in each layer. Alternating membrane protein stacks are found in, for example, the electrocyte cells of electric eels in which the transmembrane proteins are asymmetrically distributed across two primary membranes that, when added in series, can generate potentials of ≈600 V …”
Section: Introductionmentioning
confidence: 99%
“…[92,93] Several immobilized heme proteins yield well-defined electrochemical and electrocatalytic responses. [100,[117][118][119] The most extensively used heme proteins for bioelectrocatalysis are mutated and unfolded cytochromes c, myoglobins, hemoglo-bins, peroxidases, catalases, cytochrome P450, microperoxidases (Table 1). In particular, heme b is partially or completely released from the protein in case the immobilization conditions are not appropriate: as a result, the protein loses its properties and the electrochemical response is due to a non-native form of the protein or to the heme group in solution.…”
Section: Heme Proteinsmentioning
confidence: 99%
“…73 This layer-by-layer membrane system could expand the protein multilayer advantages to membrane proteins in a near native environment for bioelectrochemistry, although the electronic coupling of those proteins in this system has not been shown yet. Similarly, both the Zr 4+ anchored water-cushioned- and the floating supported lipid bilayer membrane approaches have not yet been employed in the electrochemical interrogation of membrane proteins, but they show potential.…”
Section: Lipid Bilayer Membrane Based Assembliesmentioning
confidence: 99%